2013
DOI: 10.3390/ijms14036359
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinations in the Notch Signaling Pathway

Abstract: The very conserved Notch pathway is used iteratively during development and adulthood to regulate cell fates. Notch activation relies on interactions between neighboring cells, through the binding of Notch receptors to their ligands, both transmembrane molecules. This inter-cellular contact initiates a cascade of events eventually transforming the cell surface receptor into a nuclear factor acting on the transcription of specific target genes. This review highlights how the various processes undergone by Notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 122 publications
0
57
1
Order By: Relevance
“…Thus, by manipulating the ubiquitin-proteasome pathway, HCMV is able to create an environment that will facilitate viral replication (42). Although it was previously reported that the proteasome is involved in the degradation of NICD1 and Jag1, these results were observed in cells expressing NICD1 and Jag1 exogenously (43,45,(63)(64)(65)(66). In this study, we further demonstrated that endogenous NICD1 and Jag1 proteins are also subjected to proteasomal degradation in human NPCs and that HCMV manipulates the ubiquitin-proteasome, enhancing the degradation of NICD1 and Jag1 proteins.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Thus, by manipulating the ubiquitin-proteasome pathway, HCMV is able to create an environment that will facilitate viral replication (42). Although it was previously reported that the proteasome is involved in the degradation of NICD1 and Jag1, these results were observed in cells expressing NICD1 and Jag1 exogenously (43,45,(63)(64)(65)(66). In this study, we further demonstrated that endogenous NICD1 and Jag1 proteins are also subjected to proteasomal degradation in human NPCs and that HCMV manipulates the ubiquitin-proteasome, enhancing the degradation of NICD1 and Jag1 proteins.…”
Section: Discussioncontrasting
confidence: 50%
“…The E3 ligases of Numb, Deltex1, SEL-10, and Neural1 have previously been shown to be involved in the regulation of Notch receptors or ligands via the proteasome (43,45,63,64,66). We found that RNA levels of Numb, Deltex1, SEL-10, and Neural1 NPCs.…”
Section: Discussionmentioning
confidence: 51%
“…E3 ubiquitin ligases are the only enzymes in the ubiquitination process to be specific for the substrate. 29,73 Notch-ICD contains a canonical PEST sequence, which is associated with short lifetime molecules 29 since it is associated with phosphorylation and ubiquitination. 74 The present study identifies a novel mechanism for Int3 regulation of mammary gland development through the direct effects of GSK3b.…”
Section: Discussionmentioning
confidence: 99%
“…Notch receptors and their ligands are potential substrates for ubiquitin addition by E3 ligases. [27][28][29] It has been demonstrated that Notch-ICD is rapidly polyubiquitinated and degraded through the proteasomal pathway, and the E3 ubiquitin ligase accounting for these modifications is Fbw7/Sel-10. [30][31][32] To elucidate the mechanism by which Gleevec inhibits Notch signaling, we established in vitro and in vivo systems using cell lines and transgenic mice.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation